Right to Freedom of Expression v. Reputation Protection (Based on ECtHR Practice Materials) - Tetiana M. Alforova; Mariia M. Koba; Oksana V. Lehka; Andrii M. Kuchuk (Age of Human Rights Journal, 2022)
The urgency of the study is stipulated by the necessity to clarify the criteria allowing courts to determine a balance between the right to freedom of expression (Article 10 of the Convention for the Protection of Human Rights and Fundamental Freedoms) and the right to reputation protection as part of the right to privacy (Article 8 of the Convention for the Protection of Human Rights and Fundamental Freedoms), given the complex nature and equivalence of these rights on conditions of a a democratic society. The purpose of the article is to elucidate, through the European Court of Human Rights practice, the provisions allowing defamation cases to be resolved and additional criteria that can be used to consider such cases to be formed. The research is based on the perception of human rights as natural, inalienable and equal human opportunities, which are universal in nature, but may have a regional content, allowing us to talk about the social and cultural nature of law in general. The study takes into account the implicit nature of the Convention for the Protection of Human Rights and Fundamental Freedoms provisions, which enshrine the relevant human rights, respectively, it is the decisions of the European Court of Human Rights that are “filling” these rights with the “content”. The principle of the Convention’s norms dynamic interpretation is taken into account by the Court, which ensures the effectiveness of human rights institutions and a modern understanding of the content of protected rights. The article clarifies that the criteria for finding a balance between the right to freedom of expression and reputation protection are the following: the content of the publication; degree of public interest in disseminated information; the degree of publicity of the interested person, the form and consequences of the publication, the method of obtaining information, the behavior of the interested party to the publication; as additional criteria for determining the balance between the right to freedom of expression and the protection of reputation, it is suggested to use the purpose of the publication (whether, the publication aims to create a “platform” for discussion of public interest or is used as a means of black PR or this interest is limited to unhealthy curiosity), as well as the results of linguistic examination.